2009
DOI: 10.4103/0019-5359.49076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified team based learning method for teaching general embryology to 1styear medical graduate students

Abstract: BACKGROUND AND AIMS:To encourage student participation in the learning process, the authors introduced a modified team based learning (TBL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 18 publications
0
41
0
1
Order By: Relevance
“…The Nexus Portal at Mayo Medical School (USA), allows multimedia use to share reflections, knowledge, and deductions from dissection ses-sions which students are comfortable utilizing (Durosaro et al, 2008). Similarly, team-based learning (TBL; Vasan et al, 2009) received overall positive feedback from 317 students when evaluating their preference for these sessions and teamwork irrespective of the grades attained with strongly positive internal consistencies (Cronbach's alpha 5 0.908 and 0.884, respectively) and with reproducible success in other countries like India (Shankar and Roopa, 2009).…”
Section: Peer-peer Partnershipsmentioning
confidence: 99%
“…The Nexus Portal at Mayo Medical School (USA), allows multimedia use to share reflections, knowledge, and deductions from dissection ses-sions which students are comfortable utilizing (Durosaro et al, 2008). Similarly, team-based learning (TBL; Vasan et al, 2009) received overall positive feedback from 317 students when evaluating their preference for these sessions and teamwork irrespective of the grades attained with strongly positive internal consistencies (Cronbach's alpha 5 0.908 and 0.884, respectively) and with reproducible success in other countries like India (Shankar and Roopa, 2009).…”
Section: Peer-peer Partnershipsmentioning
confidence: 99%
“…The success of peer teaching is thought to be connected to the ability of peer tutors and tutees to communicate more effectively and, therefore, improve the learning environment (Allen and Boraks, 1978). Peer teaching has been used in a variety of guises including peer-assisted learning, team-based learning (TBL) and reciprocal peer teaching, and in many different areas of health education and the biosciences (Krych et al, 2005;Tariq, 2005;Gill et al, 2006;Secomb, 2007;Evans and Canavan, 2008;Shankar and Roopa, 2009). Within anatomy, peer teaching has been widely recognized as a valuable approach for learning and has been effectively incorporated into medical, dental, and healthcare curricula (Nnodim, 1997;Brueckner and MacPherson, 2004;Youdas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with extant literature which revealed that TBL strengthens the attitudinal as well as cognitive foundation of the students. 7,10 This type of teaching not only improves the basics of any topic but also provides scope to think at higher levels of cognition (critical thinking) as evidenced in the present study wherein assurance test questions were related to basics while the group assignment exercises included case scenarios. A similar concept was reported in a study which showed that active learning activities like this one were successful in teaching the student's knowledge needed to formulate therapeutic recommendations.…”
Section: Discussionmentioning
confidence: 74%
“…Team based learning (TBL) is one such new strategy used in various curricula in India and world-wide. [4][5][6][7] TBL was originally developed by Larry Michaelsen for business schools. 8 It is a learner-centered, instructor led strategy with individual and group accountability process and involves small teams to work together to solve problems.…”
Section: Introductionmentioning
confidence: 99%